Insect Consumption in Indigenous Communities of Central America - Cruz-Dubón, Jose Adalid; Costa Neto, Eraldo Medeiros; de Azevedo Koch, Elmo Borges (Ethnobiology Letters, 2025)
Insect consumption, known as entomophagy, is an ancient practice that has recently garnered attention as a sustainable food alternative considering the global food crisis. A literature review was conducted on insect consumption among Indigenous communities in Central America, a region renowned for its biological and cultural diversity. The aim was to catalog, for the first time, the insect species consumed by these indigenous peoples. Various search engines, including Google Scholar, Mendeley, Scopus, and Web of Science, were used, focusing on articles in English and Spanish available until June 2024. The findings revealed a total of 15 edible species across five orders with a notable predominance of the order Hymenoptera. Consumption practices involve the harvesting of larvae and adults at different stages of development with larvae being particularly prized. Additionally, the review explores ongoing initiatives in Guatemala, Honduras, and Costa Rica that aim to implement trade in crickets and mealworms as an alternative food source. This study underscores the significance of preserving and valuing Indigenous knowledge regarding entomophagy, particularly in the context of food insecurity.